2017
DOI: 10.3126/ijasbt.v5i4.18083
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Green Microalgae, Scenedesmus sp. MCC26 and Acutodesmus obliquus MCC33 Isolated From Industrial Polluted Site Using Morphological and Molecular Markers

Abstract: Two unicellular green microalgae, were isolated from Amani Shah Nallah (Jaipur, India) that receives discharge of dyeing industries. Preliminary morphological characterization using light microscopy showed ovoid, fusiform shape of cells with single to two celled coenobia in a culture suspension. Transmission electron microscopy (TEM) analyses depict abundant chloroplast located at the periphery of the cell, a pyrenoid as well as nucleus is visible in the centre. A well developed cell wall with many layers is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…1 a, 2 a and 3 a) respectively. Other studies have observed similar cellular morphological alterations in Scenedesmus sp after exposure to mutagen (Akgül et al 2017 ; Beherepatil and Deore 2013 ; Sarwa and Verma 2017 ). The cell elongation, cell fusion and pairing of cells could be ascribed to the effect of the UV radiation on S. vacuolatus during cellular development (Choi et al 2017 ; Colina et al 2020 ).…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…1 a, 2 a and 3 a) respectively. Other studies have observed similar cellular morphological alterations in Scenedesmus sp after exposure to mutagen (Akgül et al 2017 ; Beherepatil and Deore 2013 ; Sarwa and Verma 2017 ). The cell elongation, cell fusion and pairing of cells could be ascribed to the effect of the UV radiation on S. vacuolatus during cellular development (Choi et al 2017 ; Colina et al 2020 ).…”
Section: Resultssupporting
confidence: 63%
“…Moreover, the cell's morphological modification, especially the concave shape, could also improve the photosynthetic activities through improved angulation of the light ray on the cell wall. Similarly, the non-damage to the green chlorophyll pigment is an indication of the cell integrity not been damaged, this desirable since chlorophyll is a photosynthetic apparatus (Choi et al 2017 ; Sarwa and Verma 2017 ). The findings in this study were consistent with earlier studies on using UV light radiation for microalgae mutagenesis (Carino et al 2022 ; Colina et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The freshwater microalgae AO was selected for the experiments, as a typical representative of photosynthetic microalgae. These microalgae strains were identified in the water bodies contaminated with industrial effluents [ 19 ]. The AO culture was obtained from the Culture Collection of Algae at Göttingen University ( Sammlung von Algenkulturen der Universität Göttingen , SAG) (Strain number 276-1).…”
Section: Methodsmentioning
confidence: 99%
“…Classic morphological taxonomy includes the use of traits observable with light microscopy, such as arrangement of cells, appearance of chloroplasts, shape and size of cells, pattern of cells, appearance of chloroplasts and mode of division. [14][15][16] For the enrichment phase, this strain was cultured in an Erlenmeyer flask using a modified synthetic medium (BG-11) of Stanier et al 17 with the following composition: NaNO 3 1.5 g L −1 , K 2 HPO 4 0.04 g L −1 , KH 2 PO 4 0.2 g L −1 , EDTA 0.001 g L −1 , iron citrate 0.001 g L −1 , citric acid 0.006 g L −1 , Na 2 CO 3 0.02 g L −1 with 1 mL of stock metal solution per liter of BG-11 medium, composed of CO(NO 3 ) 2 0.08 g L −1 , CuSO 4 0.08 g L −1 , ZnSO 4 0.02 g L −1 , MnSO4.H2O 1.8 g L −1 , H 2 O, H 3 BO 3 2.85 g L −1 . Inoculum (10%, v/v) was added to the culture, which was left for 14 days in front of a window under natural light (mean light level was 83.72 μmol photons m −2 s −1 ).…”
Section: Isolation and Culture Of Microalgal Strainmentioning
confidence: 99%